DIRECTIVE SPEECH ACTS IN 2 SELECTED EPISODES OF NUSSA ANIMATED SERIES - Fitria, Salsabila (Universitas Brawijaya, 2023)
The purpose of this study is to find out the types of directive acts in 2 selected episodes of Nussa Animated Series on the YouTube channel entitled